The Lost of Semarang Coastal Areas due to Climate Change and Land Subsidence - Suripin .; Helmi Muhammad (International Conference on Coastal and Delta Areas, 2015)
Semarang is the capital of Central Java Province, located in the northern part of JavaIsland, Indonesia, with an area of about 374 km2 and inhabited by about 1.57 million people. It has been reported for some time that coastline of Semarang is retreated. This backwards movement is mainly due to coastal erosion triggered by climate change effects, land subsidence, and coastal structures jutting to the sea. During the last two decades (1990-2010) the annual rainfall has increased 18.66 mm per year, while the maximum daily storm increased 0.82 mm/year, and the storm intensity increased annually by 0.4 - 0.5 mm/hour. Consequently, the runoff is estimated toincrease by 8% to 30%, and the flooded area increased about 5% to 15% for the next two decades. Based on sea level data recorded in Tanjung Emas Harbor during the period of 1985 up to 2008, it was found the annual relative sea level rise and land subsidence on the station are 5.536 cm/year and 5.165 cm/year consecutively, and the sea level rise is 3.7 mm per year. Interpretation of satellite imagery in 1991 and 2009 showed that 25.6 km of the total 36.6 km is eroded. This erosion has removed the coastal plain area of 1,764.5 ha. This paper is aimed to discribe and discuss the lost of Semarang Coastal Areas and sum up with concluding remarks.